Sex differences in acute telestroke care: more to the story - Sevilis, Theresa; Avila, Amanda; McDonald, Mark; Fowler, Mariecken; Chalfin, Renata; Amir, Murtaza; Heath, Gregory; Zaman, Mohammed; Avino, Lorianne; Boyd, Caitlyn; Gao, Lan; Devlin, Thomas (Frontiers in Neurology, 2023)
Abstract Background: Previous studies have shown sex differences in stroke care. Female patients have both lower thrombolytic treatment rates with OR reported as low as 0.57 and worse outcomes. With updated standards of care and improved access to care through telestroke, there is potential to reduce or alleviate these disparities. Methods: Acute stroke consultations seen by TeleSpecialists, LLC physicians in the emergency department in 203 facilities (23 states) from January 1, 2021 to April 30, 2021 were extracted from the Telecare by TeleSpecialistsTM database. The encounters were reviewed for demographics, stroke time metrics, thrombolytics candidate, premorbid modified Rankin Score, NIHSS score, stroke risk factors, antithrombotic use, admitting diagnosis of stroke, and reason not treated with thrombolytic. The treatment rates, door to needle (DTN) times, stroke metric times, and variables of treatment were compared for females and males. Results: There were 18,783 (10,073 female and 8,710 male) total patients included. Of the total, 6.9% of females received thrombolytics compared to 7.9% of males (OR 0.86, 95% CI 0.75-0.97, p=0.006). Median DTN times were shorter for males than females (38 vs 41 mins, p<0.001). Male patients were more likely to have an admitting diagnosis of stroke, p <0.001. Analysis by age showed the only decade with significant difference in thrombolytics treatment rated was 50-59 with increased treatment of males, p= 0.047. When multivariant logistic regression analysis was performed with stroke risk factors, NIHSS score, age, and admitting diagnosis of suspected stroke, the adjusted odds ratio for females was 0.9 (95% CI 0.8, 1.01), p=0.064. Conclusion: While treatment differences between sexes existed in the data and were apparent in univariate analysis, no significant difference was seen in multivariate analysis once stroke risk factors, age, NIHSS score and admitting diagnosis were taken into consideration in the telestroke setting. Differences in rates of thrombolysis between sexes may therefore be reflective of differences in risk factors and symptomatology rather than a healthcare disparity.